Transient ischemic attacks are more than "ministrokes" - Daffertshofer, Michael; Mielke, Orell; Pullwitt, Arne; Felsenstein, Matthias; Hennerici, Michael G. (Stroke, 2004)
BACKGROUND AND PURPOSE: Transient ischemic attacks (TIAs) are warning signs of stroke. Recently, the hypothesis was raised that TIA bears a significant risk for death and dependence and requires the same complex diagnostic workup as a complete stroke. - METHODS: We prospectively collected pre- and in-hospital procedures, symptoms, outcome, complications, and therapies from a representative sample of all stroke-treating hospitals (n=82) in southwest Germany. Follow-up was attempted 6 months after discharge. End points were death or dependence in activities of daily living (Barthel Index <95, modified Rankin Scale (mRS) of 3 to 6, or institutionalization in a nursing home). - RESULTS: 1380 TIA patients and 3855 stroke patients entered the database. During hospital stay, stroke incidence was 8% for TIA patients and another 5% within the first half-year. Similarly, for ischemic stroke (IS) patients these figures were 7% and 6% (P>0.05), respectively. Two percent of TIA patients died in hospital (5% afterward) compared with 9% of stroke patients (10% afterward, P<0.001). Seventeen percent TIA compared with 38% IS patients (P<0.05) were dependent at follow-up. Whereas an estimated preexisting deficit (mRS >2) was the strongest predictor for death or disability (baseline mRS odds ratio, 4.1; 95% CI, 2.3 to 7.2), admission to a stroke unit was a valid predictor for survival and independence (odds ratio, 0.4; 95% CI, 0.2 to 0.9). - CONCLUSIONS: These data from a large, multicenter, nonselected, observational study underscore the "not so benign" prognosis for TIA patients. There is a relevant individual risk of early stroke, death, or disability in TIA patients. Management and treatment strategies are similar for both TIA and acute stroke.